1998
DOI: 10.1007/s003300050380
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic approach to arteriovenous malformations of the tongue

Abstract: Arteriovenous malformations (AVM) are developmental errors with a high complication rate because they are hemodynamically active. The aim of our study is to evaluate management of the rare subgroup of tongue AVM. From 1982 to 1994, 25 patients with AVM of the tongue presented to our department. All patients were discussed in our multidisciplinary staff consultation and were treated by embolization, surgery, or were followed-up clinically with no intervention. Thirteen patients were asymptomatic in a hemodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…Few case reports have described lingual AVM 3,4,10,11 . In this study, we have identified two clinical entities, focal lingual AVM and diffuse AVM with tongue involvement.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Few case reports have described lingual AVM 3,4,10,11 . In this study, we have identified two clinical entities, focal lingual AVM and diffuse AVM with tongue involvement.…”
Section: Discussionmentioning
confidence: 89%
“…This is thought to occur as a result of incomplete resection of the nidus with rapid recruitment and collateralization of adjacent vessels. Embolization has also been shown to aggravate lesions by stimulating vascular “steal” from remaining collateral vessels 3,8 . In both cases, recurrence is quickly apparent as the “nidus” shifts location.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations